Analysis of Effect of Nitrogen Implus GTAW Welding Pipe Material SUS 304 - Dony Perdana; Moch. Nahrul Afan I (Proceeding Of The International Seminar and Conference on Global Issues, 2016)
Tungsten  Inert  Gas  welding  is  one  of  the  widel y  used  techniques  for  joining  ferrous  and  non-ferrousmetals.  TIG welding process offers several advantages like joining of unlike metals, low heat effected zone, absence of  sl ag  etc  compared  to  MIG  welding. The  accuracy  and  qualit y  of  welded  joints  lar gel y  depends  upon  ty pe  ofpower  supply  (DCSP  or  DCRP),  welding  speed,  ty pe  of  inert  gas  used  for  shieldi ng.  This  paper  deals  with  t he investigation of effect of  use nitrogen gas to weld results.  A  good weld and flat  was obtained. The conditions inside wall of the pipe has been welded kept clean without droppings and invisible residual welds attached.  The results of x-ray can be saw great results no cavities,  photograph  obtained for welding use the nitrogen gas welding impulses better results because of its shape at the corner V filled or no weld defects in the weld metal.Keywords: TIG welding, SUS 304, impulse nitrogen, x-ray